The state of biosafety across China's CDC microbiology laboratories: insights from a nationwide survey (2021–2023) - Niu, Peihua; Sun, Zhenlu; Zhang, Ruiqing; Zhao, Yiming; Tian, Fengyu; Cheng, Ping; Zheng, Hongmei; Guo, Jianqiang; Zhang, Meng; Ma, Xuejun; Wang, Ji (Frontiers in Public Health, 2024)
Background The COVID-19 pandemic underscored the critical importance of biosafety in microbiology laboratories worldwide. In response, China has ramped up its efforts to enhance biosafety measures within its Centers for Disease Control and Prevention (CDC) laboratories. This study provides the first comprehensive assessment of biosafety practices across provincial, city, and county levels of CDC microbiology laboratories in China. Methods We conducted a nationwide cross-sectional survey from 2021 to 2023, targeting staff from microbiology laboratories within CDCs at all administrative levels in China. Stratified sampling was employed to select respondents, ensuring a representative mix across different CDC hierarchies, job titles, and academic qualifications. The survey encompassed questions on biosafety training, the presence of BSL-2 and BSL-3 laboratories, adherence to general biosafety guidelines, and management practices regarding specimens, reagents, and consumables. Statistical analysis was performed to identify significant differences in biosafety practices among different CDC levels. Results A total of 990 valid responses were received, highlighting a nearly universal presence (98.69%) of BSL-2 laboratories and a significant yet varied presence of BSL-3 laboratories across the CDC network. The survey revealed high levels of biosafety training (98.69%) and adherence to biosafety protocols. However, challenges remain in the consistent application of certain safety practices, especially at lower administrative levels. Notable differences in the management of specimens, reagents, and consumables point to areas for improvement in ensuring biosecurity. Conclusion Our findings indicate a robust foundation of biosafety practices within CDC microbiology laboratories in China, reflecting significant advancements in the wake of the Biosecurity Law's implementation. Nevertheless, the variability in adherence to specific protocols underscores the need for ongoing training, resources allocation, and policy refinement to enhance biosafety standards uniformly across all levels. This study's insights are crucial for guiding future improvements in laboratory biosafety, not just in China but potentially in other countries enhancing their public health infrastructures.